Theory of Bandura's Social Learning in The Process Of Teaching at SMA Methodist Berastagi Kabupaten Karo - Sondang Manik; Milisi Sembiring; Immanuel Padang; Lastri Manurung (LPPM Universitas HKBP Nommensen, 2022)
Learning is the process of change in human character, and these changes are manifested as an increase in the quality and quantity of behavior, such as improve skills, knowledge, attitudes, habits, understanding, skills, thinking abilities, etc. To make learning enjoyable, each class should include an activity that allows students to gain new knowledge and skills. Learning activities of this type must bridge the gap between prior knowledge held by learners and new knowledge created by them. One of the psychologists known for learning theory is Albert Bandura. Albert Bandura emphasizes the importance of observing, modeling, and imitating the behaviors, attitudes, and emotional responses of others. Social learning theory considers how environmental and cognitive factors interact to influence human learning and behavior. Albert Bandura's Social Learning emphasizes the importance of the learner develop their own knowledge or information gained from model observations the surrounding environment. The learner organizes all the information in detail code. The process of preparing each code can be repeated, allowing learners to real-time feedback can be provided. The learner's behavior is the result of competence. The learner interprets knowledge or information, imitates the model, and then recognizes process and identify desired action goals. Encourage learners to think critically and creatively. Analyzing the problem and offering alternative solutions is critical to the problem.